Hippocampal and insula volume in mild cognitive impairment with Lewy bodies. (May 2021) - Firbank, Michael J.; Durcan, Rory; O'Brien, John T.; Allan, Louise M.; Barker, Sally; Ciafone, Joanna; Donaghy, Paul C.; Hamilton, Calum A.; Lawley, Sarah; Roberts, Gemma; Taylor, John-Paul; Thomas, Alan J.
Abstract: Introduction: Diagnostic criteria for prodromal dementia with Lewy bodies have recently been published. These include the use of imaging biomarkers to distinguish mild cognitive impairment with Lewy bodies (MCI-LB) from MCI due to other causes. Two potential biomarkers listed, though not formally included in the diagnostic criteria, due to insufficient evidence, are relatively preserved hippocampi, and atrophy of the insula cortex on structural brain imaging. Methods: In this report, we sought to investigate these imaging biomarkers in 105 research subjects, including well characterised groups of patients with MCI-LB (n = 38), MCI with no core features of Lewy body disease (MCI-AD; n = 36) and healthy controls (N = 31). Hippocampal and insula volumes were determined from T1 weighted structural MRI scans, using grey matter segmentation performed with SPM software. Results: Adjusting for age, sex and intracranial volume, there were no differences in hippocampal or insula volume between MCI-AD and MCI-LB, although in both conditions volumes were significantly reduced relative to controls. Conclusion: Our results do not support the use of either hippocampal or insula volume to identify prodromal dementia with Lewy bodies. Highlights: Hippocampal and insula volumes on structural MRI were reduced in MCI compared to healthy participants. Hippocampus and insula volumes were not different in probable Lewy body MCI compared with MCI without Lewy body disease. Our results do not support the use of either hippocampal or insula volume to identify prodromal dementia with Lewy bodies.